PENGARUH MOTIVASI DAN SELF EFFICACY TERHADAP MINAT BERWIRAUSAHA MAHASISWA PRODI MANAJEMEN UNIVERSITAS SARJANAWIYATA TAMANASISWA - Tri Ratna Purnamarini; Alfiatul Maulida (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2023)
Interest in entrepreneurship requires stage and processes according to each individual. There are several factors that influence interest in entrepreneurship, including motivation and self efficacy. Motivation has a duty as a driving force to change intentions iti action, while self efficacy is needed to increase interest in entrepreneurship. This study aims to analyze the effect of motivation and self efficacy on interest in intrepreneurship of students of the Management Study Program at Sarjanawiyata Tamanasiswa University. The method used in the reseach is multiple regression analysis method. The population of this research is 6th semester students of Management Study Program at Sarjanawiyata Tamansiswa University. The technique of collecting samples using simple random sampling. The samples are students of the management Study Program at Sarjanawiyata Tamansiswa University. The data collection method was using a questionnaire via google foam using a 5 level linkert scale wich was distributed online. The result of the study explain that motivation and self efficacy have a positive and significant influence on the entrepreneurial interest of student in the Management Study Program at Sarjanawiyata Tamansiswa University.